Falling for forever [large type] - Robles, Katherine (Romance in the Park, 2024)
"Hillary needs a major change in her life. She's stifled by an entry level IT job in the Virginia suburbs and longs to move to Washington D.C. where she can make a difference in the world. When Javier comes to her rescue in Great Falls National Park, Hillary likes everything about him except for the gorgeous fiance hanging on his arm. But things are not as they seem. He enlists her help to renovate a homeless shelter, and romance blossoms over paintbrushes and pipes until a career-launching opportunity arises. Hillary can chase her dreams, but they might cost her Javier' s heart"--